A Critical discourse analysis of London's Mayor Sadiq Khan's interviews in reaction to westminster attack - Muhammad Zuhdan Rifai (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/adil,c.1